Estimation of intensity of tropical cyclone over Bay of Bengal using microwave imagery - TNJHA, T.N.; MOHAPATRA , M.; BANDYOPADHYAY, B.K. (MAUSAM, 2013)
caxky dh [kkM+h esa o"kZ 2008&2010 esa ,Q- Mh- ih- vof/k ¼15 vDrwcj ls 30 uoEcj½ ds nkSjku vk, ik¡p pØokrksa ds lw{e rjaxh; es?k fcEckofy;ksa rFkk 85 fxxkgV~tZ vko`fÙk esa izkIr fd, x, mRiknksa dh tk¡p dh xbZ gS ftlls rkieku nhfIr] rkieku nhfIr esa vfu;ferrk] dsUnz dk LFkku] lrg ij vuojr cgus okyk vf/kdre iou ¼,e- ,l- MCY;w-½ rFkk pØokrksa ds fHkUu&fHkUu fLFkfr;ksa esa muds rhozhdj.k ls lacaf/kr djdksa tSls% vonkc ¼Mh-½] xgu vonkc ¼Mh- Mh-½] pØokrh; rwQku ¼lh- ,l-½] rhoz pØokrh; rwQku ¼,l-lh-,l-½] vfr rhoz pØokrh; rwQku ¼oh-,l-lh-,l-½ vkfn dk vkdfyr dsUnzh; nkc ¼bZ- lh- ih-½ dk vkdyu fd;k tk ldsA izf{kr fd, x, nhfIr rkieku vfu;ferrkvksa dh rqyuk lS)kafrd :i ls bZ-lh-ih- ds csLV VªSd vkdyu ij vk/kkfjr nhfIr rkieku vfu;ferrk ,oa bu pØokrksa ds ckgjh nkc ds lkFk Hkh dh xbZ gSA dsUnz ds LFkku] bZ-lh-ih- ,oa lw{erajxh; fcEckoyh ds vk/kkj ij vkdfyr ,e- ,l- MCY;w- dh rqyuk csLV VªSd ,oa Hkkjr ekSle foKku foHkkx ds Mh- oksjkWd ds vkdyu ls dh xbZ gS vkSj mldk fo’ys"k.k fd;k x;k gSA pØokrh; fo{kksHk ¼lh- Mh-½ ds dsUnz ds LFkku esa varZ tSlkfd lw{erjaxh fcEckofy;ksa rFkk csLV VªSd vkdyu ds }kjk vkdfyr fd;k x;k gS] fo{kksHkksa ds rhozhdj.k ds lkFk&lkFk de gksrk tkrk gS vkSj vonkc ¼Mh-½ dh fLFkfr esa yxHkx 25 fd-eh- ls vfr rhoz pØokrh; rwQku ¼oh-,l-lh-,l-½ dh fLFkfr esa 18 fd- eh ds chp cnyrk jgrk gSA tcfd ;g varj Mh oksjkWd ds vkdyu ls dkQh vf/kd gSA lw{erjaxh; vkdyuksa ij vk/kkfjr ,e- ,l- MCY;w- vkdyu oh-,l- lh- ,l- ds nkSjku csLV VªSd vkdyuksa ls yxHkx 28 ukWV~l vf/kd vkdfyr fd;k x;k gS vkSj vonkc ¼Mh-½@pØokrh; rwQku ¼lh-,l-½@rhoz pØokrh; rwQku ¼,l- lh- ,l-½ dh fLFkfr esa ;g 6&8 ukWV~l vkdfyr fd;k x;k gSA csLV VSªd vkdyuksa ls lkisf{kd varj dks ns[kus ls irk pyk gS fd lh-,l- vkSj ,l-lh- dh fLFkfr esa lw{e rajx esa ,e-,l-MCY;w- yxHkx 12&15 izfr’kr vkSj oh-,l-lh-,l- dh fLFkfr esa yxHkx 30 izfr’kr vf/kd vkdfyr gqvk gS tcfd Mh- oksjkWd dk ,e- ,l- MCY;w- vkdyu lh- ,l-] ,l- lh- ,l- vkSj oh- ,l- lh- ,l- dh fLFkfr;ksa esa 15&18 izfr’kr de gks x;k gSA caxky dh [kkM+h ds Åij 230 dsfYou dk nhfIr rkieku vonkc ds cuus ds fy, vuqdwy gksrk gS] 250 dsfYou dk rkieku bldks pØokrh rwQku esa 260 dsfYou rhoz pØokrh rwQku esa vkSj 270 dsfYou vfr izpaM+ pØokrh rwQku esa cny nsrk gSA nhfIr rkieku ds nsgyheku ¼FkszlksYM osY;w½ ds vfHkKku ¼fMVSD’ku½ ls bl iz.kkyh ds rhoz gksus dk iwokZuqeku nsus ds fy, iz;kIr vfxze le; fey ldrk gSA blh izdkj nhfIr rkieku folaxfr 3 dsfYou ls vf/kd gksus ij pØokrh; rwQku rhoz pØokrh; rwQku esa cny tkrk gS vkSj 8 dsfYou dk rkieku bls caxky dh [kkM+h esa vfr izpaM pØokrh; rwQku ds :i esa cny nsrk gSA Microwave cloud imageries and derived products in the frequency of 85 GHz have been examined for five cyclones that occurred during FDP period (15 October- 30 November) of 2008-2010 over the Bay of Bengal to estimate the brightness temperature, brightness temperature anomaly, location of centre, maximum sustained wind (MSW) at surface level and estimated central pressure (ECP) associated with cyclones in their different stages of intensification like depression (D), deep depression (DD), cyclonic storm (CS), severe cyclonic storm (SCS), very severe cyclonic storm (VSCS), etc. Also the observed brightness temperature anomalies are compared with theoretically derived brightness temperature anomalies based on the best track estimates of ECP and outermost pressure for these cyclones. The location of centre, ECP and MSW based on microwave imagery estimates have been compared with those available from the best track and Dvorak’s estimates of India Meteorological Department and analyzed. The difference in location of the centre of cyclonic disturbance (CD) as estimated by microwave imageries and best track estimates decreases with intensification of the disturbances and varies from about 25 km in depression (D) stage to 18 km in VSCS stage whereas the difference is significantly higher in case of Dvorak estimate compared to best track estimate. The MSW based on microwave estimates is higher than that of best track estimates by about 28 knots during VSCS and 6-8 knots during D, CS, SCS stage. Considering relative difference with respect to best track estimates, the MSW is overestimated in microwave by about 12-15% in case of CS and SCS stage and by about 30% in VSCS stage while Dvorak’s MSW overestimation reduced to 15-18% during CS, SCS and VSCS stages. Brightness temperature of the order of 230 K is favourable for genesis (formation of D), 250K for its intensification into CS, 260 K for intensification into SCS and 270K for its further intensification into VSCS stage over the Bay of Bengal. Detection of threshold value of brightness temperature may provide adequate lead time to forecast intensification of the system. Similarly, when brightness temperature anomaly exceeds 3K, CS intensify into SCS and 8K, it intensifies into a VSCS over Bay of Bengal.